2016
DOI: 10.1111/petr.12652
|View full text |Cite
|
Sign up to set email alerts
|

Favorable outcome to glucocorticoid therapy for engraftment syndrome in pediatric autologous hematopoietic cell transplant

Abstract: ES is a common complication in children after auto-HCT and short-course glucocorticoid therapy is an effective and well-tolerated treatment, even in those who did not completely fulfill diagnostic criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…However, there was no clear link between the starting dose and response to treatment as summarized in Table 1. Five articles 2,12,17‐19 used a starting dose of 1 mg/kg/d, three articles 11,13,16 used a starting dose of 2 mg/kg/d, and three articles 5,23,24 used a starting dose ranging 1‐2 mg/kg/d. Konuma et al 14 reported no treatment was used for ES.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there was no clear link between the starting dose and response to treatment as summarized in Table 1. Five articles 2,12,17‐19 used a starting dose of 1 mg/kg/d, three articles 11,13,16 used a starting dose of 2 mg/kg/d, and three articles 5,23,24 used a starting dose ranging 1‐2 mg/kg/d. Konuma et al 14 reported no treatment was used for ES.…”
Section: Resultsmentioning
confidence: 99%
“…Loose stools and gastrointestinal changes are not uncommon following HSCT and may be related to the conditioning regime, GVHD, or an infective cause. Stool cultures should be attained following the first incidence of diarrhea and accurate documentation of stool loss recorded 6,9,13,16,25 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Steroids are thought to reduce the inflammatory response and the resultant capillary leak and often used in the setting of engraftment syndrome. A short course of steroids for 3–5 days was effective in children post-autologous transplant and did not increase the risk of infection ( 29 ).…”
Section: Discussionmentioning
confidence: 99%